Digital Leadership and Data-Driven Decision Making in E-Government at Diskominfo Padang City - Nurul Hidayahti Salsabilla; Padrison P; Nora Eka Putri; Adil Mubarak (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to examine digital leadership in data-driven decision-making during the e-government era, using the Office of Communication and Informatics (Diskominfo) of Padang City as the contextual framework. Digital leadership has become an urgent need for public sector organizations required to adapt to information technology transformation. This study employs a literature review method by analyzing and synthesizing relevant journals, scientific articles, and policy documents. The findings indicate that effective digital leadership requires leaders to utilize data as a systematic basis for decision-making. In the context of Diskominfo as the leading sector for e-government at the regional level, several critical factors determine successful implementation, including digital leadership competency, data infrastructure integration, and organizational culture transformation. This study recommends strengthening digital leadership capacity through training, developing integrated data systems, and transforming organizational culture toward a data-driven bureaucracy.